Antimicrobial effect of diallyl sulphide on Campylobacter jejuni biofilms. - Lu X; Samuelson DR; Rasco BA; Konkel ME; Lu, Xiaonan; Samuelson, Derrick R; Rasco, Barbara A; Konkel, Michael E (Journal of Antimicrobial Chemotherapy (JAC), 2012)
Objectives: Bacterial biofilms pose significant food safety risks because of their attachment to fomites and food surfaces, including fresh produce surfaces. The purpose of this study was to systematically investigate the activity of selected antimicrobials on Campylobacter jejuni biofilms.Methods: C. jejuni biofilms and planktonic cells were treated with ciprofloxacin, erythromycin and diallyl sulphide and examined using infrared and Raman spectroscopies coupled with imaging analysis.Results: Diallyl sulphide eliminated planktonic cells and sessile cells in biofilms at a concentration that was at least 100-fold less than used for either ciprofloxacin or erythromycin on the basis of molarity. Distinct cell lysis was observed in diallyl sulphide-treated planktonic cells using immunoblot analysis and was confirmed by a rapid decrease in cellular ATP. Two phases of C. jejuni biofilm recalcitrance modes against ciprofloxacin and erythromycin were validated using vibrational spectroscopies: (i) an initial hindered adsorption into biofilm extracellular polymeric substance (EPS) and delivery of antibiotics to sessile cells within biofilms; and (ii) a different interaction between sessile cells in a biofilm compared with their planktonic counterparts. Diallyl sulphide destroyed the EPS structure of the C. jejuni biofilm, after which the sessile cells were killed in a similar manner as planktonic cells. Spectroscopic models can predict the survival of sessile cells within biofilms.Conclusions: Diallyl sulphide elicits strong antimicrobial activity against planktonic and sessile C. jejuni and may have applications for reducing the prevalence of this microbe in foods, biofilm reduction and, potentially, as an alternative chemotherapeutic agent for multidrug-resistant bacterial strains.